Quantitative Determination of Organochlorine Pesticide Residues in Sugarcane Obtained from Hawkers in Gusau Metropolis, Zamfara State, Nigeria - MOMOH SHAIBU; S. A. ABDULLAHI (International Journal of Scientific Research and Innovative Studies, 2022)
In this research work, organochlorine pesticide residues was quantitatively determined in sugarcane juice extracts obtained from hawkers in Gusau metropolis Zamfara state, Nigeria. QuECHERS and GC-MS were used for samples extraction and analysis under standard conditions. Twenty organochlorine pesticide standard were used and only five organochlorine pesticide residues were detected in the extract namely; alpha lindane, endosulfan ether, isodrine, heptachlor epoxide and DDMU with concentration 0.0250 mg/kg, 0.0270 mg/kg, 0.0141 mg/kg, 0.0003 mg/kg, 0.0016 mg/kg respectively. The entire organochlorine pesticide residues detected are within the maximum residual limit (MRL) except alpha lindane and endosulfan ether that are little higher than 0.02 mg/kg of MRL. The presence of organochlorine pesticides residues in the sugarcane juice extract shows that farmers are still using the banned organochlorine pesticide for pest control, therefore, routine monitoring of pesticide residues is necessary for information on the level of environmental pollution, in order to minimize health risk to human.